2017
DOI: 10.4236/ajps.2017.84045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Trichoderma harzianum</i> in Combination with Fungicides in Controlling Gray Mould Disease (<i>Botrytis cinerea</i>) of Strawberry

Abstract: The effects of biofungicide formula containing the biocontrol agent Trichoderma harzianum (Jn14) as wettable powder in combination with the fungicides pyrimethanil and a mixture of cyprodinil and flydioxonil on Botrytis cinerea of strawberry in vitro, in vivo and in greenhouse were studied. The pathogen B. cinerea was more affected in vitro by low concentrations of the fungicides tested above 0.4 µg ml −1 than the bioagent T. harzianum (Jn14). The later was almost insensitive to pyrimethanil. In the same direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Also, they indicated that 1.0% for sodium benzoate showed high radial growth reduction by 63.3% and 61.1%, respectively, compared to the untreated control. Such results are in harmony with those reported by (Menzel et al, 2016 andBarakat andAl-Masri, 2017).…”
Section: Laboratory Experiments 1the In Vitro Effect Of Certain Saltsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, they indicated that 1.0% for sodium benzoate showed high radial growth reduction by 63.3% and 61.1%, respectively, compared to the untreated control. Such results are in harmony with those reported by (Menzel et al, 2016 andBarakat andAl-Masri, 2017).…”
Section: Laboratory Experiments 1the In Vitro Effect Of Certain Saltsupporting
confidence: 92%
“…It is an excellent source of vitamin C, which contains an average 40-90 mg. Egypt is considered the third largest producer of strawberry in the world after the United States and Spain (Wu et al, 2012). In Egypt, strawberry is one of the most important vegetable crops for local consumption and exportation (Embaby et al, 2016, andBarakat andAl-Masri, 2017). Unfortunately, strawberry is affected by several plant diseases that affect its yield and quality in both the pre-and post-harvest stages.…”
Section: Introductionmentioning
confidence: 99%
“…A similar combination with a 10-fold reduction of the fungicide dithianon was more effective in controlling scab (caused by Venturia inaequalis) than the fungicide alone at the recommended dose in field trials of apple [56]. Moreover, plant extracts of Inula viscosa combined with the fungicide iprodione at a reduced rate were as effective against B. cinerea on bean plants as the full dose of fungicide [57].…”
Section: Combinations Of Fungicides With Biological Antagonistsmentioning
confidence: 95%
“…Where MGR represents mycelium growth rate, d 2 is the average diameter of the colony in cm after 72 h, d 1 is the average diameter of the colony after 24 h, t is the time of incubation [ 37 ]. The experimental design was a completely randomised design (CRD) with five replicates.…”
Section: Methodsmentioning
confidence: 99%